CONNOTATIVE AND DENOTATIVE MEANING OF ADELE'S SONG LYRICS “EASY ON ME” - Wawat Srinawati (STKIP Muhammadiyah Bogor, 2021)
There are different types of meaning in language, one of the branches of linguistics that deals with meaning is semantics. Semantics is known as the study of meaning. This study aims to analyze the connotative and denotative meanings contained in song lyrics, expressions of feelings or ideas usually expressed through song lyrics. The song selected for this research data is Adele's song, entitled